Holocene land cover and population dynamics in Southern France. (May 2019) - Berger, Jean-François; Shennan, Stephen; Woodbridge, Jessie; Palmisano, Alessio; Mazier, Florence; Nuninger, Laure; Guillon, Sebastien; Doyen, Elise; Begeot, Carole; Andrieu-Ponel, Valérie; Azuara, Julien; Bevan, Andrew; et al.
This paper describes long-term changes in human population and vegetation cover in southern France, using summed radiocarbon probability distributions and site count data as population proxies and information from fossil pollen cores as a proxy for past land cover. Southern France is particularly well-suited to this type of study as a result of previous programmes of intensive survey work and excavation in advance of large-scale construction. These make it possible to calibrate the larger scale occupation patterns in the light of the visibility issues created by the burial of archaeological sites beneath alluvial sediments. For purposes of analysis, the region was divided into three biogeographical zones (BGZ), going from the Mediterranean coast to the middle Rhône valley (MRV). All the different population proxies in a given zone show broadly similar patterns of fluctuation, though with varying levels of resolution. The long-term patterns in the different zones all show significant differences from the overall regional pattern, but this is especially the case for the non-Mediterranean middle Rhône area. Cluster analysis of pollen samples has been carried out to identify the main regional land cover types through the Holocene, which are increasingly dominated by open types over time. A variety of other pollen indicators show evidence of increasing human impact through time. Measures of human impact correlate strongly with the population proxies. A series of thresholds are identified in the population–human impact trajectory that are related to other changes in the cultural sequence. The lack of independent climate data for the region means that its impact cannot currently be assessed with confidence. However, for the later periods, it is clear that the incorporation of southern France into larger regional systems played a major role in accounting for changes in land cover and settlement.